PERSPECTIVE OF ISLAMIC LAW IN COUNTER-RADICALISM IN INDONESIA - Muhyidin, Muhyidin (Masalah-Masalah Hukum, 2023)
Wrong understanding of jihad and mis-implementation in a non-war atmosphere (daar as salam), has given rise to radical attitudes that lead to violent acts of terrorism. Studies in this field are generally from the point of view of positive law and human rights as part of counter-radical thinking. This paper explains the background of thoughts that give rise to radical attitudes, and shows approaches to criminal law and Islamic law in the context of counter-radicalism. The legal instruments discussed are Law No. 15 of 2003 and Law No. 5 of 2018. The discussion of Islamic law takes the perspective of fiqh jinayat which is related to rebellion against the state and murder, the conditions for imposing rebellion and murder, and punishment for the perpetrators. Through this explanation, it is hoped that it can correct the meaning of the arguments for jihad which are the roots of radical attitudes.